Transformasi Islam dan Peradaban sebagai Pilar Wawasan Kebangsaan di Indonesia - Siregar, Uzair Nazri (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
Indonesian national insight is an important foundation in maintaining the integrity of the Unitary State of the Republic of Indonesia (NKRI) amidst religious, cultural, and ethnic diversity. One of the main pillars supporting this national insight is the transformation of Islam as the majority religion, which not only shapes the spiritual aspects of society but also contributes significantly to the development of national civilization. The transformation of Islam in Indonesia reflects the dynamic journey of normative values into contextual, adaptive, and inclusive socio-political and cultural practices. This article aims to examine Islam's contribution to the formation of a harmonious national civilization and its role as a pillar of national integration. The method used is a descriptive qualitative approach with a literature study of historical, religious, and socio-cultural sources. The results show that Islam in Indonesia has undergone significant transformations from the kingdom era and colonialism to the reform era, adapting its teachings to local dynamics without losing its universal substance. Islamic civilization has contributed significantly to the birth of the Islamic boarding school education system, intellectual traditions, interfaith tolerance, and the spirit of unity in the struggle for independence. Islam also fosters national consciousness through modern Islamic organizations such as Muhammadiyah and Nahdlatul Ulama, which play an active role in the nation-building process. In conclusion, the transformation of Islam and its civilization has become a cultural and spiritual force that strengthens Indonesia's national vision in facing global challenges and internal disintegration.